Role of Digitalization in Financial Inclusion: An Analysis of Gender Digital Divide in North India - Gupta, Minu (My University, 2024)
The study aims to examine the degree of Sustainable Digital Financial Inclusion of employees of Banking sector and IT sector. The study also examines the presence of gender difference in Sustainable Digital Financial Inclusion among employees reflected through Gender Digital Divide. Banking sector imparts the knowledge of Digital Banking, and IT sector develops the Digital Banking applications. Currently, the banking industry relies heavily on Information and Technology infrastructure to increase profitability. As large number of banking tasks have been computerized, contribution of Information and Technology sector has become an essential part of the banking sector, where they are responsible for technology-related tasks on banks' networks, databases, and servers. This explains the combined role of the Banking sector and Information and Technology sector in providing Digital Financial Services, which leads to Digital Financial Inclusion. The model's antecedents were extracted from extended version of Unified Theory of Acceptance and Use of Technology (UTAUT2). The idea was to significantly deepen various UTAUT2 constructs in order to meet the demands of this rapidly changing, technologically driven Banking and IT sector. This research is motivated by the void left by previous researchers in understanding the determinants of Digital Banking Adoption Intention by employees of Banking sector and IT sector; as their digital inclusivity influences the Digital Financial Inclusion of clients. The study contributes by clubbing the financial sector and the technological sector. The primary data for the study was gathered from employees of Indian banking sector and IT sector using a questionnaire. The current study includes 600 employees (300 from banking sector and 300 from IT sector). The data collection method employed was stratified random sampling. The study population consisted of employees working in top 6 IT companies and 6 Banks of regions of North India. To test the hypotheses, Partial Least Square Structural Equation Modeling have been performed. Additionally, a study of the indirect effect of the Digital Banking Adoption Intention between Drivers influencing Digital Banking and Sustainable Digital Financial Inclusion for employees reveals a significant mediation effect on Sustainable Digital Financial Inclusion for workers in both sectors. In contrast to female bank employees (β: 0.516, p ≤ 0.001), the mediation effect VIII for male bank employees (β: 0.550, p ≤ 0.001) is higher. Furthermore, compared to female IT employees (β: 0441, p ≤ 0.001), male IT employees have a larger mediation effect (β: 0.479, p ≤ 0.001). This shows that the Digital Banking Adoption Intention has a significant mediation effect on Sustainable Digital Financial Inclusion. It also shows that the mediation effect is stronger for male employees in both sectors. The model explained 85.3% of the variance for male bank employees, and 85% variance for their female counterparts. 82.1% of the variance in Sustainable Digital Financial Inclusion for male IT employees and 63.5% for female counterparts; for male bank employees, it explained. The model's predictive power rose as a result of mediation. Concerning the Gender Digital Divide, gender gap in Digital Banking adoption and gender gap in Digital Financial Inclusion, authors conclude that a significant gender gap is found in Digital Banking adoption and its effect on Sustainable Digital Financial Inclusion through mediation of Digital Banking Adoption Intention, where men have outperformed their women counterparts in both sectors. It shows a gender-based variation in mediation effect in both sectors. The study also aimed to examine the barriers causing Gender Digital Divide among employees of both sectors. Through EFA, barriers were classified as: Financial Knowledge Barriers, Functional Barriers, and Privacy Barriers. Barriers classified explained 74.78% of the variation. Functional barriers are the most critical barriers in DB adoption, reflecting Gender Digital Divide, followed by Privacy Barriers, and Financial Knowledge Barriers. The management of the bank ought to take this into consideration and give female staff members specialized training on various digital platforms so they can better serve female clients. This action might raise women's DFI levels across the country. Similarly, more women should be hired and trained for application development roles by upper management in IT companies where women make up a sizable portion of the workforce. This will support the creation of websites and applications that appeal to women. The study has limitations of selective sampling and limited geographical reach. The study's scope could be expanded by increasing the sample size. Also, to improve applicability, future studies might concentrate on IT firms and banks from other areas as well.
Keywords: Financial Inclusion; Digital Banking; Digital Divide; Banks; Gender; Digital Banking